OPTIMIZATION OF WORKSHOP FACILITIES IN VOCATIONAL SCHOOL TO SERVE THE PRACTICUM OF LIGHT VEHICLE ENGINE MAINTENANCE - SUJADI, SUJADI; Faza, Ibnu Nur; Sriyono, Sriyono; Noor, Ridwan Adam M (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2022)
This research is motivated by the lack of optimal practical infrastructure in vocational schools on the subject of light vehicle engine maintenance. This study aims to optimize the practice facilities at SMK PU Negeri Bandung. The method used in this research is a quantitative descriptive method with instruments of observation, interviews and documentation, then the collected data is processed statistically. The results showed that the light vehicle technique had the smallest ratio between the area of the room and the number of students among other skill competencies. The level of availability of infrastructure for an engine work area of 96 m², an electrical work area of 48 m², a chassis work area of 64 m², an instructor's room work area of 48 m² and an overall workshop area of 256 m² so that if categorized as standard workshop infrastructure at SMK PU Negeri Bandung 25% less than the standard BSNP and Permendiknas RI No. 40 of 2008. Therefore, optimization is done by making a practice schedule to increase the arrangement and use of practical infrastructure to 80%.